Understanding the local values of trees and forests: a strategy to improve the urban environment in Hawassa City, Southern Ethiopia. Issue 2 (3rd April 2019) - Molla, Mikias Biazen; Mekonnen, Abrham Belay
ABSTRACT: Urban trees and urban forests play important roles in the ecology of human habitats and the wider environment. However, these roles may be undermined by the community and resulting decline in urban forest cover over time. This study analyses the value of trees and forests in improving the urban environment and assesses the awareness level of communities of the value of trees and forests in Hawassa City, Ethiopia. A cross-sectional survey design was applied and data were obtained from a structured questionnaire survey of 200 respondents and from twenty-two interviews with key stakeholders. The collected data were analysed using descriptive statistics, chi-square test, and multiple linear regression models. Educational level and an annual income of the residents had strongly significant (p = 0.000) association with the awareness level of residents of the value of urban trees and forest. About 99% of the respondents noted that trees and forest have shading and cooling effects, 93% perceived trees as for recreational value, and 88% of them stated that trees and forests are important for city beautification. The chi-square test showed that there is a significant difference between forest-related services users and non-users. Multiple regression models indicated that sex, age, annual income and education level were found statistically significant (p = 0.000) and positively affect respondents' level of understanding about the value of urban trees and forest in improving the urban environment. Urban trees and forests have also played crucial roles, around reducing Urban Heat Island effect, improving shading and cooling services and reducing soil erosion, and this was statistically significant (p = 0.001). Lack of awareness on the use of urban trees and forest, limited public support for urban green infrastructure, poor policy and strategic guidance were found to be influential factors affecting the management of urban trees and forest. Rapid city-expansion has also contributed to lesser understanding and poor management practices of urban trees and forest. This implies that comprehensive inventories of urban trees and forest resources across the city should be conducted using geospatial technologies. Thus, systematic and integrated stakeholder involvement is crucial to address those issues at local, regional and national levels.